Improving children’s language skills through online learning during covid-19 pandemic - Robingatin, Robingatin; Saugi, Wildan; Susan, Susan (JECCE (Journal of Early Childhood Care and Education), 2020)
The present study was done to find out the children’s language skill improvement in online learning during Covid-19 pandemic at TK IT Bunga Harapan. In order to maintain children’s language development amid the pandemic, online learning was implemented. Qualitative approach was applied. We involved 12 preschool students as the participants of the study. The data were collected through observation, interview, and documentation. Children’s language skill improvement in TK Bunga Harapan was proven by the decrease in number of students suffering from speech delay, from 4 students (25%) to 1 student (6.25%) out of 12 students. This improvement was noticed after teachers conducted online learning activities that provided children with experience to make videos stimulating them to communicate and speak. With regard to the assessment, teachers used anecdotal notes by observing the children’s development through videos they made.